A study on the factors affecting the acceptance of internet banking: case study on Seremban area / Nurul Ariffah No’man and Nur Atika Rosli - No’man, Nurul Ariffah; Rosli, Nur Atika (2013)
Information technology Services is considered as the key driver for the changes taking place around the world. Internet banking (IB) is the latest and most innovative service and is the new trend among the consumers. The shift from the formal banking to e-banking has been a 'leap' change(Safeena, Date, & Kammani, 2011). This study determines the factors influencing the consumer’s adoption of internet banking in Seremban and hence investigates the influence of acceptance on use of IB. It is an essential part of a bank’s strategy formulation process in an emerging economy like Malaysia. Survey based questionnaire design was carried out. The results have supported the hypothesis. 150 questionnaires have been distributed among the public in Seremban area. The data obtained were analyzed in SPSS 20.0 which involvesreliability test, frequencies, Pearson Correlation Coefficient and regression analysis. The study also attempt to identify the most essential factors among those investigated; trust, attitude and attraction Based on the findings, trust is found to have no significant relationship towards the acceptance of internet banking but both attitude and attraction were found to have a significant relationship towards acceptance of internet banking. Moreover, attraction is found to be the most influential factors in affecting the acceptance of internet banking. The findings achieved in this study will be of interest for financial institution in order to increase their customer in internet banking services.